Corporate culture as a strategic driver of employee performance: a systematic review of empirical evidence - Nofrizal Nofrizal; Yunia Wardi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study aims to systematically review empirical evidence on the role of corporate culture as a strategic driver of employee performance. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this study analyzed 40 peer-reviewed open-access articles published between 2020 and 2025 and indexed in reputable databases. The findings reveal that corporate culture significantly influences employee performance through shared values, leadership behavior, communication climate, and learning orientation. A strong and adaptive corporate culture enhances employee motivation, work engagement, productivity, and organizational citizenship behavior. This review also identifies gaps in existing research, particularly the limited use of longitudinal designs and the lack of focus on digital and hybrid work cultures. The study contributes to the literature by providing an integrated understanding of how corporate culture drives employee performance and offers strategic insights for organizational development and human resource management